Manumycin A suppresses exosome biogenesis and secretion via targeted inhibition of Ras/Raf/ERK1/2 signaling and hnRNP H1 in castration-resistant prostate cancer cells. (1st November 2017) - Datta, Amrita; Kim, Hogyoung; Lal, Madhu; McGee, Lauren; Johnson, Adedoyin; Moustafa, Ahmed A.; Jones, Jennifer C.; Mondal, Debasis; Ferrer, Marc; Abdel-Mageed, Asim B.
Abstract: Emerging evidence links exosomes to cancer progression by the trafficking of oncogenic factors and neoplastic reprogramming of stem cells. This necessitates identification and integration of functionally validated exosome-targeting therapeutics into current cancer management regimens. We employed quantitative high throughput screen on two libraries to identify exosome-targeting drugs; a commercially available collection of 1280 pharmacologically active compounds and a collection of 3300 clinically approved compounds. Manumycin-A (MA), a natural microbial metabolite, was identified as an inhibitor of exosome biogenesis and secretion by castration-resistant prostate cancer (CRPC) C4-2B, but not the normal RWPE-1, cells. While no effect was observed on cell growth, MA attenuated ESCRT-0 proteins Hrs, ALIX and Rab27a and exosome biogenesis and secretion by CRPC cells. The MA inhibitory effect is primarily mediated via targeted inhibition of the Ras/Raf/ERK1/2 signaling. The Ras-dependent MA suppression of exosome biogenesis and secretion is partly mediated by ERK-dependent inhibition of the oncogenic splicing factor hnRNP H1. Our findings suggest that MA is a potential drug candidate to suppress exosome biogenesis and secretion by CRPC cells. Highlights: There are no known approved drugs targeting exosome biogenesis and secretion by castration-resistant prostate cancer (CRPC) cells. MA suppresses exosome biogenesis and secretion via inhibition of Ras/Raf/MEK/ERK1/2 signaling in CRPC cells. The Ras-dependent MA suppression of exosome biogenesis and secretion is partly mediated via an ERK-dependent inhibition of hnRNP H1 in CRPC cells. MA is a potential adjuvant therapeutic drug in patients presenting with CRPC.